Penanaman Nilai Islami Anak Berbasis Literasi Media Visual Bergambar - Halimah, Nur; Futri, Mayana; Harahap, Sartika Dewi; Arifah, Dinil; Hidayah, Riski; Larasati, Larasati; Sofiah, Sofiah; Suraya, Suraya (Universitas Muhammadiyah Magelang, 2026)
This study employed a qualitative approach with a descriptive design aimed at obtaining an in-depth understanding of the utilization of illustrated visual media in early childhood literacy activities. The research subjects were children enrolled in one of the Early Childhood Education (PAUD) institutions. This approach was selected to comprehensively describe the naturally occurring learning process and to capture children's responses during the implementation of literacy activities. Data were collected through participatory observation and documentation techniques. Observation was conducted to directly examine children’s engagement, learning interactions, and the implementation of illustrated visual media in the literacy process. Documentation served as supporting data, including activity records, children’s work, and relevant instructional archives. Data analysis was carried out through the stages of data reduction, systematic data display, and conclusion drawing to generate meaningful findings. The findings revealed that the use of illustrated visual media in literacy activities made a positive contribution to enhancing children’s engagement and active participation during the learning process. The media effectively captured children’s attention, stimulated their interest in learning, and facilitated their understanding of the Islamic values conveyed. Therefore, the use of illustrated visual media can be considered an effective instructional strategy to support literacy development as well as the internalization of values in early childhood education.